Ag2S nanoparticles anchored on P-doped g-C3N4: a novel 0D/2D p-n 2 heterojunction for superior photocatalytic inactivation of 3 multidrug-resistant E. coli - Wanshu Yan; Pingping Hu; Yiguo Jiang; Xiuquan Xu; Xianfeng Ma; Mengru Wang; Xinyue Bao (Materials Research Express, 2022)
Photocatalytic inactivation has been proved to be an effective strategy to eliminate pathogenic bacteria in water. Herein, a novel 0D/2D p-n heterojunction of Ag _2 S-anchored P-doped g-C _3 N _4 (Ag _2 S/PCN) were constructed by a simple two-step process coupling one-pot calcination and ultrasonic-assisted synthesis. The photocatalytic performance of as-prepared Ag _2 S/PCN composites was investigated by inactivating multidrug-resistant E. coli under visible light irradiation. The results indicated that Ag _2 S/PCN-5 possessed outstanding photocatalytic inactivation activity and superior stability, which could completely inactivate 7.0 log E. coli cells within 60 min. The enhanced photocatalytic activity of Ag _2 S/PCN-5 was mainly attributed to the elevated visible-light response and improved production and transfer of photoexcited charges. In addition, the free radicals trapping experiments results revealed that h ^+ and •O _2 ^− were predominantly responsible for the efficient inactivation activity. Finally, according to the 0D/2D structure and energy band configuration analysis, the enhanced p-n type heterojunction photocatalytic inactivation mechanism of Ag _2 S/PCN was discussed in detail.